Unions and collective bargaining in Sub-Saharan Africa: Some insights from quantitative studies - Uwe Jirjahn (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2025)
This article reviews quantitative research on unions and collective bargaining in Sub-Saharan Africa. It discusses the consequences of unions for wages, inequality, economic performance and employer-employee relations. The article also highlights the role of unions in society, a role that goes beyond the economic sphere. Moreover, the article discusses evidence on how the specific situation in Sub-Saharan Africa influences unionization and collective bargaining. The informal sector, ethnic divide and globalization entail serious threats to workers' unionization. The increasing influence of China and neoliberal policy prescriptions by the International Monetary Fund and the World Bank are challenging factors, too.
Keywords: J51; J52; F66; O10; O55; 330; Africa; Industrial Relations; Political Spillover; Informal Sector; Ethnic Diversity; Globalization